Liver transplantation for unresectable pancreatic neuroendocrine tumors with liver metastases in an era of transplant oncology - Shimata, Keita (Gland Surg, 2018)
Patients with pancreatic neuroendocrine tumors (pNETs) very often present with a metastatic disease at the first diagnosis. Liver transplantation (LT) for unresectable pNET with liver metastases (pNETLM) has been described to prolong survival in highly selected patients, although outcomes were worse than those of patients who underwent LT for gastrointestinal NETLM (GI-NETLM). In this review, several proposed criteria are described with their rationale and controversies. Most of the data used to establish these criteria do not reflect the recent improvements of non-surgical treatments that has changed the landscape of treatment for pNETs, including the development of peptide receptor radionuclide therapy and molecular-targeted agents (sunitinib and everolimus). Properly designed studies are necessary to define the role of down-staging and bridging therapy prior to LT incorporating systemic chemotherapy using these molecular-targeted agents. Also, given the indolent nature of low or intermediate grade pNETs, the best endpoint to compare the efficacy of each treatment option for patients with pNETLM has yet to be determined. Lastly, the definition of “unresectable” remains ambiguous. The indication of the conventional technique of two-staged liver resection with portal vein embolization or the new technique of associating liver partition and portal vein ligation for staged hepatectomy to expand the resectability of wide-spread metastatic liver tumors has been controversial. In an era of transplant oncology, LT should be the last resort for patients who are considered unresectable and otherwise untreatable after an exhaustive multidisciplinary team discussion by all experts in the field. In conclusion, although its long-term outcomes have been promising, the role of LT for unresectable pNETLM as a curative or palliative treatment remains unclear. A well-designed randomized control study is required to elucidate the clinical impact of LT for pNETLM.